Construction methods and biomedical applications of PVA-based hydrogels - Zhong, Yi; Lin, Qi; Yu, Han; Shao, Lei; Cui, Xiang; Pang, Qian; Zhu, Yabin; Hou, Ruixia (Frontiers in Chemistry, 2024)
Polyvinyl alcohol (PVA) hydrogel is favored by researchers due to its good biocompatibility, high mechanical strength, low friction coefficient, and suitable water content. The widely distributed hydroxyl side chains on the PVA molecule allow the hydrogels to be branched with various functional groups. By improving the synthesis method and changing the hydrogel structure, PVA-based hydrogels can obtain excellent cytocompatibility, flexibility, electrical conductivity, viscoelasticity, and antimicrobial properties, representing a good candidate for articular cartilage restoration, electronic skin, wound dressing, and other fields. This review introduces various preparation methods of PVA-based hydrogels and their wide applications in the biomedical field.